Cryptic bioactivity capacitated by synthetic hybrid plant peptides - Yuki Hirakawa (Nature Portfolio, 2017)
Peptide hormones play versatile roles in plant development and environmental responses. Here the authors report the engineering of a synthetic plant peptide that acts on meristems through interaction with both the CLV1 and TDR/PXY receptors ofArabidopsis thaliana.